Synthesis of Rare Earth Metal Oxides Based on Monasite Sand with pH Variations - Anisa Indriawati; Herman Aldila; Verry Andre Fabiani (Department of Chemistry - Universitas Bangka Belitung, 2020)
In the island of Bangka Belitung, the presence of monazite is quite abundant, monazite minerals contain rare earth metals. Rare Earth Metals are groups of elements that have similar properties, for example neodymium, cerium, lanthanum, and others. Rare earth metal applications are very potential in various fields. In this research, the synthesis of rare earth metals by sol gel method at pH variations of 5.5, 6.5 and 7.5 was carried out. In this case, only changes in the levels of P2O5, La2O3, CeO2, and Nd2O3 compounds were observed. The results showed an increase in levels of rare earth metals. This is indicated by the increase in La2O3 levels by 4,421% from the initial level at pH 7.5 CeO2 which has increased levels by 7,166% at pH 7.5, and Nd2O3 which has increased levels of 5.116% at pH 6.5. On the other hand, of P2O5 has decreased significantly (22.037%) Keyword: Monasite, Rare Earth, Sol Gel, pH